Narratives in Research and Interventions on Cyberbullying among Young People - Vandebosch, Heidi; Green, Lelia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes innovative ways to do research about, and design interventions for, cyberbullying by children and adolescents. It does this by taking a narrative approach. How can narrative research methods complement the mostly quantitative methods (e.g. surveys, experiments, ....) in cyberbullying research ? And how can stories be used to inform young people about the issue and empower them? Throughout the book, special attention is paid to new information and communication technologies, and the opportunities ICTs provide for narrative research (e.g. as a source of naturally occurring stories on cyberbullying), and for narrative health interventions (e.g. via Influencers). The book thus integrates research and insights from the fields of cyberbullying, narrative methods, narrative health communication, and new information and communication technologies.
Introduction -- Part 1 Cyberbullying -- Part 2 Narratives -- Part 3 Narrative Research Methods in Cyberbullying Research -- Part 4 Narratives in Cyberbullying Interventions Aimed at Young People -- Part 5 Narratives and Community-level Responses.
Keywords: Communication; School Psychology; Education; Children; Media and Communication; School Psychology; Childhood Education